What makes us strong: Urban aboriginal perspectives on wellness and strength - Quressette, Seanna (quressettes) (Author); Van Uchelen, Collin P. (Author); Davidson, Sara Florence (Author); Brasfield, Charles R. (Author); Demerais, Lou H. (Author) (Canadian Journal of Community Mental Health, 1997)
The limitations of a needs orientation for aboriginal mental health planning are evaluated in terms of the discrepancy between First Nations and western medical paradigms of health. We propose an alternative approach that focuses on how aboriginal people conceptualize wellness and describe their strengths. This provides a focus for initiatives that promote well-being by enhancing strengths rather than concentrating solely on deficits. We illustrate this approach by highlighting the indigenous knowledge of urban First Nations people in Vancouver's Downtown Eastside neighbourhood. We conclude that supporting existing strengths promotes wellness in holistic, culturally appropriate, and empowering ways. Final article published.